COMPUTATIONAL AND EXPERIMENTAL INSIGHTS INTO HYDROGEN STORAGE IN METAL-ORGANIC FRAMEWORKS (MOFs) - Ardi Azhar Nampira; Ava Lee; Marcus Tan (Yayasan Adra Karima Hubbi, 2025)
The transition to a hydrogen economy is critically dependent on the development of safe and efficient onboard hydrogen storage materials. Metal-Organic Frameworks (MOFs) have emerged as highly promising candidates due to their exceptionally high surface areas and tunable pore environments. This study aimed to combine computational modeling with experimental validation to elucidate the key structural factors governing hydrogen storage capacity in MOFs. A dual approach was employed, using Grand Canonical Monte Carlo (GCMC) simulations to predict hydrogen uptake in a series of MOFs with varying pore sizes and metal centers, followed by experimental synthesis and gas sorption analysis to validate the computational findings. The results revealed a strong correlation between the simulated and experimental data, confirming that both high surface area and optimal pore size ( 10-15 Å) are crucial for maximizing physisorption. The GCMC simulations accurately predicted that MOFs with open metal sites exhibit enhanced hydrogen binding energies. This research concludes that a combined computational and experimental approach provides powerful predictive insights, confirming that tailoring pore geometry and introducing strong adsorption sites are key strategies for the rational design of next-generation MOFs for high-density hydrogen storage.